Effectiveness of Internal Control Measures for Preventing Employee’s Fraud in Public Secondary Schools in Ebonyi State Nigeria - Joy Amaechi Okeke - Ezeanyanwu; Sylvia Chinwe Okere (Action Research Journal Indonesia (ARJI), 2025)
This study investigated the extent of effectiveness of internal control measures in preventing employee’s fraud in public secondary schools in Ebonyi State, Nigeria. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. Survey research design was adopted for the study. The population of the study comprised 225 principals of public secondary schools in Ebonyi State. The entire population was used as the sample size of the study. The instrument for data collection was a validated structured questionnaire developed by the researcher. The test of reliability of the instrument using Cronbach Alpha yielded coefficient of 0.76, 0.74, for clusters B1 to B2 respectively. Out of 225 copies of questionnaire administered only 222 copies were retrieved, therefore going for 98.6% return. Data collected for the study were analyzed using descriptive statistics of mean, standard deviation and t-test. The mean value was used to answer the research questions while the standard deviation was used to ascertain the homogeneity or otherwise the respondents' response. The t-test was used to test the null hypothesis at 0.05 level of significance. The findings revealed that demotion strategy is highly effective in preventing employee fraud in public secondary schools in Ebonyi State. However, the findings showed that head count payment is also highly effective in preventing employee fraud, indicating that regular verification of staff can prevent fraudulent activities. Based on the findings, the researcher recommends that government, principals, and school administrators should implement as matter of urgency these strategies to prevent employees’ fraud in public secondary schools in Ebonyi State.